Pension funds and capital market development in Africa: The role of institutional quality - Kathryn A. A. O Assefuah; Joshua Yindenaba Abor; Saint Kuttu; Lordina Amoah (Cogent Economics & Finance, 2023)
This study investigates the effect of pension funds (PF) and institutional quality (IQ) on capital market development in 48 African countries. Using a system GMM regression, the study found that the interaction between PF and IQ significantly negatively affects capital market development. The results of the study suggest that PF in Africa contributes positively to overall financial development, and pension fund managers (PFM) seem to be focusing more on other financial market assets than capital markets. It was concluded that IQ may act as a risk management tool. It is therefore recommended that policies on strong IQ should be put in place to enable fund managers to meet their obligations towards the principal (contributor) during retirement. The study recommends that policymakers should integrate the capital markets by ensuring the cross-listing of some of the national exchanges and cross-border investment and also encourage investments in alternative asset classes.
Keywords: 330; capital market; financial development; fund managers; institutional quality; pension funds